On the Delta-hedging of the option price on future from the Black-Scholes equation - Amnuay Kananthai (2018)
© 2018 by the Mathematical Association of Thailand. All rights reserved. At present the option on future is popular one for trading but there are some problems of risk. So the minimizing of risk which is call the hedging is needed. In this paper we studied such hedging by using the Delta-hedging which is popular at present. We found the new results which having the interesting properties. We hope that such results may be useful in the research area the Financial Mathematics.